Analysis on the Transboundary Impact Assessment System and Practice of Hydropower Development on the Main Mekong River. Issue 1 (May 2021) - Zhao, Jin; Guo, Lidan; Lin, Jinghan; Dou, Rui; Huang, Yujia; Bao, Yunxiang
Abstract: The relevant documents and regulations on procedures and contents of transboundary impact assessment issued by the Mekong River Commission are combed. Combining with analysis of existing practice, experience and shortcomings of transboundary impact assessment in hydropower development on the main Mekong River is discussed. The results show that the transboundary impact assessment procedure of the Mekong River Commission is gradually improving. What's more, the management mode of transboundary impact has gradually changed from paying attention to the prior evaluation to the whole process management. But there is no universal assessment standard for the transboundary impact, and the comprehensive assessment of the transboundary impact caused by hydropower development is lacked.